(untitled) - 1949-; Clements, Andrew; Selznick, Brian (New York, 2001)
After twelve-year-old Natalie writes a wonderful novel, her friend Zoe helps her devise a scheme to get it accepted at the publishing house where Natalie's mother works as an editor.
Keywords: Authorship; Fiction; Publishers and publishing; Fiction